2017
DOI: 10.1111/jop.12568
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of Mycoplasma salivarium in oral lichen planus tissue

Abstract: BackgroundOral lichen planus (OLP) is a T‐cell‐mediated inflammatory disease; however, its exact etiology is unknown. Hyperkeratosis is often observed in OLP lesions. Previous studies have revealed the localization of Mycoplasma salivarium in the epithelial cells of oral leukoplakia with hyperkeratosis. Herein, we investigated the presence of M. salivarium in OLP tissue by immunohistochemistry to determine the causative factor of OLP.MethodsForty‐one formalin‐fixed, paraffin‐embedded samples obtained from 31 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…reported that Mycoplasma salivarium was detected in 58.5% of OLP tissues by immunohistochemistry using an antibody to M. salivarium . The bacteria were localized intracellularly in epithelial cells although intracellular or extracellular localization in the lamina propria was not clear . Several Mycoplasma species, including M. salivarium , were detected among the buccal mucosal microbiota analyzed by our group, although there was no difference in relative abundance between control and OLP groups.…”
Section: Association With Bacterial Infectionmentioning
confidence: 57%
“…reported that Mycoplasma salivarium was detected in 58.5% of OLP tissues by immunohistochemistry using an antibody to M. salivarium . The bacteria were localized intracellularly in epithelial cells although intracellular or extracellular localization in the lamina propria was not clear . Several Mycoplasma species, including M. salivarium , were detected among the buccal mucosal microbiota analyzed by our group, although there was no difference in relative abundance between control and OLP groups.…”
Section: Association With Bacterial Infectionmentioning
confidence: 57%
“…S2). M. salivarium, the species detected in 58.5% of OLP tissues from Japanese patients 10 , was found in three OM samples at <0.1% but in none of the OT samples.…”
Section: Resultsmentioning
confidence: 89%
“…Recently, several studies have suggested that microorganisms may trigger or be responsible for sustaining or exacerbating the chronic course of OLP [ 32 34 ]. Epithelial barrier dysfunction may precede intracellular infection of basal epithelial cells with bacteria, virus, or possibly fungus.…”
Section: Discussionmentioning
confidence: 99%